Novel adaptive reclosing scheme using wavelet transform in distribution system with battery energy storage system. (April 2018) - Seo, Hun-Chul; Rhee, Sang-Bong
Highlights: This paper proposes a novel adaptive reclosing scheme in the distribution system with BESS. A new index using wavelet transform is proposed to detect the fault clearance. The system configuration and algorithm for the proposed adaptive reclosing scheme are discussed. The proposed technique is verified by simulating the various fault clearing time and fault types. Abstract: Most distribution systems are operated in an unbalanced state; hence, neutral currents can be generated by unbalanced currents in three-phase four-wire distribution systems. This paper proposes a novel adaptive reclosing scheme that uses the neutral current in a distribution system with a battery energy storage system (BESS). The BESS, which operates as an uninterruptible power supply, is connected to the load side. In the proposed scheme, there are two circuit breakers (CBs) at the source and load sides. The wavelet transform of neutral current is performed using symlets 5 mother wavelet at level 2. The summation of the absolute values of level 2 detail coefficients is calculated, and the absolute value of the differentiation of this summation is proposed as a new index for detecting fault clearance. The CB at the source side is reclosed after detecting fault clearance using ADSum. Then, the CB at the load side is reclosed after the completion of a synchronism check. To verify the proposed scheme, the BESS is modeled using the ATP-ElectroMagnetic Transients Program. In addition, various simulations are conducted according to fault types and fault clearance times. Simulation results show that successful adaptive reclosing is possible in the distribution system with the BESS.